Kekaburan Pengaturan Pasal 201 Ayat (5) Undang-Undang Nomor 10 Tahun 2016 Tentang Pemilihan Gubernur, Bupati, Dan Walikota Terhadap Akhir Masa Jabatan Kepala Daerah - Gusman, Delfina (Faculty of Law, Andalas University, 2024)
The postponement of the regional elections in 2022 and 2023 has resulted in a fairly long transition period, and most autonomous regions will experience vacancies in regional head positions for a relatively long period of time, namely 2 to 3 years until the 2024 simultaneous regional elections are held. One form of implementation of the concept of democracy is holding regional head elections (Pilkada) simultaneously nationally. There has been legal ambiguity in Article 201 paragraph (5) of Law Number 10 of 2016 concerning the Election of Governors, Mayors and Regents whose term of office of regional heads ends in 2023. This research is legal research (doctrinal research). The results of this research explainThe appointment of Acting Regional Heads is not carried out randomlyelectical pointed which must be participated in by election by the community but is only appointed to fill vacancies in regional government so that regional government activities can run quickly. Second, Legal Ambiguity Article 201 paragraph (5) of Law Number 10 of 2016 results in legal uncertainty and legal guarantees for applicants who serve as regional heads and will harm their political positions and even programs that have been promised will not be fully implemented.